Traditional Herbal Medicines, Bioactive Metabolites, and Plant Products Against COVID-19: Update on Clinical Trials and Mechanism of Actions - Alam, Safaet; Sarker, Md. Moklesur Rahman; Afrin, Sadia; Richi, Fahmida Tasnim; Zhao, Chao; Zhou, Jin-Rong; Mohamed, Isa Naina (Frontiers in Pharmacology, 2021)
SARS-CoV-2 is the latest worldwide pandemic declared by the World Health Organization (WHO), and there is no established anti-COVID drug to combat this notorious situation. By affecting the global public health sector, this viral infection has created a disastrous situation associated with high morbidity and mortality rates along with remarkable cases of hospitalization because of its tendency to be high infective. These challenges forced researchers and leading pharmaceutical companies to find and develop cures for this novel strain of coronavirus. Besides, plants have a proven history of being notable wellsprings of potential drugs, including antiviral, antibacterial, and anticancer therapies. As a continuation of this approach, plant-based preparations and bioactive metabolites along with a notable number of traditional medicines, bioactive phytochemicals, traditional Chinese medicines, nutraceuticals, Ayurvedic preparations, and other plant-based products are being explored as possible therapeutics against COVID-19. Moreover, the unavailability of effective medicines against COVID-19 has driven researchers and members of the pharmaceutical, herbal, and related industries to conduct extensive investigations of plant-based products, especially those that have already shown antiviral properties. Even the recent invention of several vaccines has not eliminated doubts about safety and efficacy. As a consequence, many limited, unregulated clinical trials involving conventional mono- and poly-herbal therapies are being conducted in various areas of the world. Of the many clinical trials to establish such agents as credentialed sources of anti-COVID-19 medications, only a few have reached the landmark of completion. In this review, we have highlighted and focused on plant-based anti-COVID clinical trials found in several scientific and authenticated databases. The aim is to allow researchers and innovators to identify promising and prospective anti-COVID agents in clinical trials (either completed or recruiting) to establish them as novel therapies to address this unwanted pandemic.